2022
DOI: 10.3390/s22155843
|View full text |Cite
|
Sign up to set email alerts
|

Periodicity Intensity of the 24 h Circadian Rhythm in Newborn Calves Show Indicators of Herd Welfare

Abstract: Circadian rhythms are a process of the sleep–wake cycle that regulates the physical, mental and behavioural changes in all living beings with a period of roughly 24 h. Wearable accelerometers are typically used in livestock applications to record animal movement from which we can estimate the activity type. Here, we use the overall movement recorded by accelerometers worn on the necks of newborn calves for a period of 8 weeks. From the movement data, we calculate 24 h periodicity intensities corresponding to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In addition, a daily pattern might refer to a day-to-day pattern, or to a within-day pattern. Softer terms, such as periodicity (van Dixhoorn et al , 2018; Rhodes et al , 2022) and ‘in relation to time of day’ (Stoye et al , 2012) were also found. A term like ‘periodicity’ opens up to a wider understanding of a concept, which includes some regularity, but lacks immediate information on the length of period.…”
Section: Terminologymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a daily pattern might refer to a day-to-day pattern, or to a within-day pattern. Softer terms, such as periodicity (van Dixhoorn et al , 2018; Rhodes et al , 2022) and ‘in relation to time of day’ (Stoye et al , 2012) were also found. A term like ‘periodicity’ opens up to a wider understanding of a concept, which includes some regularity, but lacks immediate information on the length of period.…”
Section: Terminologymentioning
confidence: 99%
“…Both nighttime rumination time and the ratio between daytime and nighttime rumination time, as well as the difference between recorded and expected rumination time per 2-h, were important features for the prediction of healthy vs. diseased cows using classification models. As suggested by Rhodes et al (2022), computing and visualizing the intensity of a 24-h pattern will provide information regarding the strength of periodicity of the individual that is not detectable directly from movement data. By applying the theory of lack of robustness being a sign of upcoming disease to the lying distribution in Figure 2, it becomes apparent that cow 120 might be in need of extra supervision.…”
Section: Individual Patternsmentioning
confidence: 99%
“…Indicators of homeostatic integrity include the periodicity of biorhythms and the dynamic complexity of system functions such as behaviours and affective state. The degree of synchronisation of behaviours and physiological variables within the 24 h circadian cycle is decreased when current and future health status and some production outcomes are poorer in freegrazing sheep (Nunes Marsiglio Sarout et al 2018), calves (Veissier et al 1989;Sun et al 2021;Rhodes et al 2022) and cows (van Dixhoorn et al 2018;Wagner et al 2021). Many methods have been developed for analysing the strength of periodicity of biorhythms (e.g.…”
Section: Analysis Of Physiological and Behavioural Variablesmentioning
confidence: 99%
“…Many methods have been developed for analysing the strength of periodicity of biorhythms (e.g. Scheibe et al 1999;Wagner et al 2021;Rhodes et al 2022). In addition to changes in periodicity of biorhythms, the temporal complexity of behaviours (Asher et al 2009) is decreased during periods of stress and disease in livestock (Burgunder et al 2018;Herborn et al 2020), zoo animals (Miller et al 2020) and wild species (MacIntosh et al 2011).…”
Section: Analysis Of Physiological and Behavioural Variablesmentioning
confidence: 99%
“…The regularity of the sleep-wake cycle is important not just for humans but for other living animals. We investigated the strength of the circadian periodicity of newborn calves on a commercial farm and how that strength of periodicity changes throughout their first 6-8 weeks after birth [31]. Many animals including cattle are behaviourally synchronised with herds coordinating reactions to external zeitgebers [32] so our interest in this use case is in the periodicity intensity of the circadian rhythm for the herd as a whole as well as for individual calves.…”
Section: Periodicity Intensity In Calf Movementsmentioning
confidence: 99%